EFFECT OF CuO NANOPARTICLES ON SEED GERMINATION AND SEEDLING GROWTH IN ECHINACEA PURPUREA IN VITRO. - M. H. Ahmed; Z. S. Omran (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to examin the effect of CuONPs on both seeds germination, seedling growth and comparing the method of soaking and adding to the culture medium, The research was implemented at PTC. Lab. College of Biotechnology - Al Nahrain University, during 2022 and 2023. The experimental design was factorial within CRD. It was included five experments and ten replicates (4X3). first experment was by using Sodium Hypochlorite (0.0, 1, 2 and 3%) with (5, 10, 15min) duartion time. The second experment was CuONPs (0, 25, 50, 75mg,L‾¹ ) combined with (3,6,9 and 12 day) Time duration, same factors wre examined after soaking seeds with CuONPs which represented the third experment, fourth and fifth experments soaked before culture seeds were cultured respictively with CuONPs (0.0, 25, 50, 75mg,L‾¹ ) for 1hour then culturing them on MS media. Results showed full reduction in the contamination rate of the selected E. purpurea explant recorded in 3% sodium hypochlorite at 10 and 15min. the highest rate of seeds germination were a chieved with CuONPs of 50 mg, L‾¹ for 9 days rated 7.80 germinated seeds in MS media culture method, at the soaking method the results clarify the highest CuONPs 75 mg, L‾¹ combined with 6,9 and 12 days of soaking a chieved the highest germination rate 10.0 seeds (100% germination).The results also showed that 50% of CuONPs increases shoot numbers 8.6 explant and dry weight 198 mg. 25% of CuONPs achieve the best shoot length 14.5 cm. in seeds soaking results showed the best shoot Nu. 8.7, shoot length 9.7 cm. and dry weight 204 mg. when seeds was soaked in 75 mg, L‾¹ of CuONPs.